Implementasi Digital Receptionist berbasis Web dan Android - Besus Maula Sulthon; Eva Zuraidah (Journal of Computer System and Informatics (JoSYC), 2021)
Along with the rapid development of Information Technology and its wide application to various aspects or fields of business, information technology has also been widely used by industry or other organizations. Its utilization aims to facilitate users and provide efficiency in a business field in carrying out its activities. The situation of the coronavirus pandemic demands that we optimally not come into contact with other people or keep our distance. From the facts, many companies or offices still carry out manual receptions using receptionist services which will result in guests having to change their identities to get office access, and the high level of information technology facilities and infrastructure is not matched by the awareness of the Indonesian people to use them optimally. From these problems, the researcher proposes research as an alternative solution in the form of designing web and Android application systems to replace the receptionist function or what is called Digital Receptionist using a structured approach, Design Method, PHP, and MYSQL with web and android based application development. The results achieved are expected to be able to avoid touching hands or keep a distance and increase the efficiency and effectiveness of the guest reception process. The conclusion obtained is that with this Digital Receptionist system, besides being able to increase the efficiency and effectiveness of the guest reception process and avoid touching hands or keeping a distance